Tomato spotted wilt orthotospovirus influences the reproduction of its insect vector, western flower thrips, Frankliniella occidentalis, to facilitate transmission. Issue 7 (24th February 2020) - Wan, Yanran; Hussain, Sabir; Merchant, Austin; Xu, Baoyun; Xie, Wen; Wang, Shaoli; Zhang, Youjun; Zhou, Xuguo; Wu, Qingjun
Abstract: BACKGROUND: Tomato spotted wilt orthotospovirus (TSWV), one of the most devastating viruses of ornamental plants and vegetable crops worldwide, is transmitted by the western flower thrips, Frankliniella occidentalis (Pergande), in a persistent‐propagative manner. How TSWV influences the reproduction of its vector to enhance transmission and whether infection with TSWV changes the mating behavior of F. occidentalis are not fully understood. RESULTS: TSWV‐exposed thrips had a significantly longer developmental time than non‐exposed individuals. More importantly, increased developmental time was predominantly associated with adults, a stage critical for dispersal and virus transmission. In addition, TSWV‐exposed F. occidentalis produced substantially more progeny than did non‐exposed thrips. Interestingly, most of the increase in progeny came from an increase in males, a sex with a greater dispersal and virus transmission capability. Specifically, the female/male ratio of progeny shifted from 1.3–7.0/1 to 0.6–1.1/1. As for mating behavior, copulation time was significantly longer in TSWV‐exposed thrips. Finally, females tended to re‐mate less when exposed to the virus. Resistance to re‐mating may lead to reduced sperm availability in females, which translates to a larger number of male progeny under a haplodiploid system. CONCLUSION: These combined results suggest that TSWV can influence the developmental time, mating behavior, fecundity, and offspring sex allocation of its vector F. occidentalis to facilitate virus transmission. As such, a monitoring program capable of the earlier detection of the virus in host plants and/or its insect vector, thrips, using double‐antibody sandwich enzyme‐linked immunosorbent assay (DAS‐ELISA), real time quantitative polymerase chain reaction (RT‐qPCR) or virus detection strips might be beneficial for long‐term, sustainable management. © 2020 Society of Chemical Industry Abstract : TSWV‐exposed western flower thrips changed their sex allocation strategy, in which more males were produced. The female/male ratio of progeny shifted from 1.3–7.0/1 to 0.6–1.1/1.